Separation process essentials - Lane, Alan M. (Boca Raton, FL : CRC Press/Taylor & Francis Group, 2020)
"This book reviews and builds on material learned in the first chemical engineering courses such as Material and Energy Balances and Thermodynamics as applied to separations. It focuses on vapor-liquid systems such as distillation, absorption, and stripping and studies extraction and membrane separations. It does not attempt to be a comprehensive treatment of all separation processes but refers readers to other more complete works and is designed for a one semester course. It relies heavily on example problems including completely worked and explained problems followed by "Try This At Home" guided examples. Most examples have accompanying downloadable Excel spreadsheet simulations"--
OCLC-licensed vendor bibliographic record.
Keywords: Separation (Technology); Extraction (Chemistry); SCIENCE / Chemistry / Industrial & Technical; TECHNOLOGY / Engineering / Chemical & Biochemical; TECHNOLOGY / Material Science